The effects of eccentric conditioning stimuli on subsequent counter-movement jump performance - Ong, J. H.; Lim, J.; Chong, E.; Tan, F. (The Journal of Strength and Conditioning Research, 2016)
The eccentric phase in a stretch-shortening cycle is an important determinant of subsequent concentric performance, but there is little information on high-intensity eccentric preconditioning. The purpose of this study was to determine the effects of varying degrees of eccentric conditioning stimuli on subsequent counter-movement jump (CMJ) performance. Fourteen participants (age, 28.5 ± 5.0 years; height, 172.7 ± 6.7 cm; body mass, 74.3 ± 11.9 kg) performed CMJ trials on 3 separate test sessions at least 96 hours apart in a crossover randomized counterbalanced study. Peak power (Ppeak) and vertical displacement (Dmax) were measured before and at 3, 6, 9, and 12 minutes (T3-12) postcontrol (0RM), 105% (105RM), and 125% (125RM) 1RM eccentric hip sled. The differences in vertical jump performance parameters between 0RM and eccentric preloading conditions (105RM and 125RM) and the differences within condition between control time point and posteccentric load time course T3, T6, T9, and T12 were analyzed for statistical significance via unequal variance t statistic. Statistical significance was set at p = 0.05. Significantly higher Ppeak, compared with 0RM (4143 ± 754 W) was seen at T3 and T6 in both 105RM (4305 ± 876 and 4237 ± 842 W) and 125RM (4314 ± 848 and 4264 ± 768 W). Compared with 0RM (42.2 ± 7.8 cm), corresponding Dmax, was also significantly improved at T3 in both 105RM (44.5 ± 7.3 cm) and 125RM (44.3 ± 8.3 cm) and at T6 in 105RM (44.7 ± 7.7 cm). Compared with baseline (43.2 ± 7.2 cm), there was significantly higher Dmax at T3 and T6 in 105RM. In conclusion, high-intensity preconditioning eccentric contraction at 105 and 125% 1RM was effective in improving CMJ power and height at 3 and 6 minutes after loading. Thus, power athletes and coaches can consider the application of eccentric preconditioning in warm-up routines.